1994
DOI: 10.1007/bf00006237
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of manganese in selected tissues of the freshwater crab, Potamonautes warreni (Calman), from industrial and mine-polluted freshwater ecosystems

Abstract: Manganese concentrations in water and sediments of the Bronkhorstspruit River, Nooitgedacht Dam and especially in the Natalspruit River, did not fall within stated limits for the protection of aquatic life. Tissue manganese concentrations in Potamonautes warreni from the Natalspruit River were generally higher than those in the tissues of crabs from the other two aquatic ecosystems. The highest mean manganese tissue concentration in crabs from the three systems was detected in the carapace (587+ 445 pg g-1 wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The mean Cu concentrations in whole crabs from the two localities were very similar to concentrations found in P. warreni from a polluted stream (Steenkamp et al 1994). Individual variation was, however, much greater in P. perlatus and Our study indicated that the digestive gland contained the highest concentrations of Cu irrespective of seasonal variation in environmental levels.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The mean Cu concentrations in whole crabs from the two localities were very similar to concentrations found in P. warreni from a polluted stream (Steenkamp et al 1994). Individual variation was, however, much greater in P. perlatus and Our study indicated that the digestive gland contained the highest concentrations of Cu irrespective of seasonal variation in environmental levels.…”
Section: Discussionsupporting
confidence: 76%
“…Elevated levels of trace metals in crabs can allow for improved chemical analysis, making them useful for biomonitoring purposes (Steenkamp et al 1994). However, deductions about the extent to which these levels reflect environmental contamination at a specific point in time, is not warranted without due consideration of temporal factors and factors governing uptake and elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the extending of this loss is uncertain (MANCE, 1990). STEENKAMP et al (1994) found variation in the carapace manganese concentration of Potamonautes warreni, likely related to the stage in the moult cycle. HILMY et al (1988) reported that mature crabs, Portunus pelagicus accumulated higher concentrations of zinc than immature crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different parts of the world showed that industrial and other pollution of water sources was associated with increased levels of metals such as lead, nickel, copper, cadmium, manganese, zinc, and iron. Iron concentrations are usually not very high in surface waters (in the order of 0.01-5.00 mg/L), but accumulation of the metal occurs to very high levels in their sediments (80-164000 mg/kg), [18][19][20] aquatic vegetation, 19 and zooplankton. 20,21 We believe that these findings and conclusions have important implications in the interpretation of our toxigenicity findings since the iron levels reported in these studies overlap with those that enhanced CT production in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Iron concentrations are usually not very high in surface waters (in the order of 0.01-5.00 mg/L), but accumulation of the metal occurs to very high levels in their sediments (80-164000 mg/kg), [18][19][20] aquatic vegetation, 19 and zooplankton. 20,21 We believe that these findings and conclusions have important implications in the interpretation of our toxigenicity findings since the iron levels reported in these studies overlap with those that enhanced CT production in our study. In contrast, the possible impact of excess iron on CT production by V. cholerae, which was the main objective of this study, was not an objective of investigations by these workers.…”
Section: Discussionmentioning
confidence: 99%